Review artikel: Uji Efektivitas Ekstrak Daun Teh Hijau Sebagai Antibakteri - Nur Komala Fitri; Arline Rahmadianti Kusumawardhani (Journal of Pharmaceutical and Sciences, 2023)
Introduction: Tea is a plant that comes from the Theaceae family, the part of the tea plant that is commonly used as traditional medicine is the leaves, empirically drinking steeped tea leaves has properties for lowering blood pressure, preventing cancer and can reduce stress. Green tea is a type of tea leaf obtained by heating or using hot steam on older tea leaves compared to white tea. Purpose: the effectiveness of green tea leaf extract as an antibacterial based on several studies that have been conducted. Method: Article review with publication range 2013-2023. Results: Green tea leaf plants contain flavonoid compounds with the catechin subclass, catechins have antibacterial activity. Grkeen tea leaves will be extracted and then the catechin compounds will be separated from the main extract using KLT. Conclusion: From the awareness that has been made, it can be said that the catechin compounds contained in green tea leaf extract have antibacterial benefits, this is indicated by the presence of a clear zone in the experiment with the diffusion disc, then the clarity in the direct inoculation test, and the decrease in the number of bacterial colonies is measured by using a colony counter.